mNGS-identified cellulitis due to quinolone-resistant Edwardsiella tarda: a case report - Wang, Xuejin; Gu, Danxia; Zhang, Liwei; Wu, Yuchen; Zhang, Rong; Li, Kewei; Ren, Haitao (Frontiers in Medicine, 2024)
Edwardsiella tarda is frequently isolated from aquatic animals and environments.While human infections caused by E. tarda are rare, some extraintestinal infections can be severe. This case report describes a patient with cellulitis of the right upper extremity of unknown origin. mNGS indicated that the patient was infected with E. tarda. Antimicrobial susceptibility testing revealed that the isolate was resistant to quinolones and trimethoprim/sulfamethoxazole. The isolate, positive for four virulence genes (fimA, gadB, mukF, sodB), was confirmed to be virulent using the Galleria mellonella larvae model. Following early pus drainage and a 9-day course of imipenem, the patient ultimately recovered. This case report aims to illustrate the presentation, diagnosis, and management of an uncommon cellulitis caused by drugresistant, virulent E. tarda.